RASONAPINDA: A CLINICAL EVALUATION IN MANAGEMENT OF AMAVATA (RHEUMATOID ARTHRITIS) - Abhinav; Srivastava, V.K.; Rai, N.P. (International Journal of Ayurveda and Pharma Research, 2015)
Amavata is a very common disorder affecting a much larger population. The disease closely resembles Rheumatoid Arthritis on the basis of clinical manifestations. In the present study, we have considered Rheumatoid Arthritis parallel to Amavata and studied the effect of Rasona Pinda, a traditional Ayurvedic drug. 40 patients of Amavata were selected and randomly divided into two groups A and B. Group A was trial group and Group B was control group. Group A received Rasona Pinda and group B as control group received Indomethacin orally, duration of treatment for both the groups was 45 days with a follow up on every 15th day. The drug was selected as it is described in Chakradatta Amavatadhikara and also owing to its properties. Results were assessed according to a specially prepared grading system for pain, swelling, stiffness, tenderness, general functional capacity, walking time, grip power, pressing power, etc and changes observed in laboratory profile. Significant improvement was seen in symptoms in group A, and on comparing the results in the two groups it was found that the difference was highly significant with improvement in almost all the symptoms in group A. and also, it was found that the drug was free of side effects and showed improvement in the general health of the patient. The study suggests that Rasona Pinda can be a reliable alternative in the management of Amavata.